(untitled) (Third Sector Social Economic Review, 2020)
Although cryptocurrencies have not yet been accepted as an official currency worldwide, their using tends to increase day by day by both individuals and institutions. The rapid spread of the use of cryptocurrencies has increased the acceptance of money as an investment tool outside of the exchange function. This situation raises the need to question the relationship between share markets and cryptocurrencies. Accordingly, the study aimed to test the existence of a causality relationship between Bitcoin, which is an alternative investment tool and the largest crypto currency, and selected share markets. In a study conducted using daily data between July 19, 2010 and January 10, 2020, Lee-Strazicich Unit Root The test was conducted and the causality relationship was tested with the Toda-Yamamoto causality test. According to the findings obtained at the end of the study, while a causality relationship was determined from the Bitcoin series to the S & P500 series; no causality relationship has been found towards the Bist100, Bovespa, Invsaf40 and Merval markets.